Lipids in the inner membrane of dormant spores of Bacillus species are largely immobile - Cowan, Ann E. (National Academy of Sciences, 2004)
Bacterial spores of various Bacillus species are impermeable or exhibit low permeability to many compounds that readily penetrate germinated spores, including methylamine. We now show that a lipid probe in the inner membrane of dormant spores of Bacillus megaterium and Bacillus subtilis is largely immobile, as measured by fluorescence redistribution after photobleaching, but becomes free to diffuse laterally upon spore germination. The lipid immobility in and the slow permeation of methylamine through the inner membrane of dormant spores may be due to a significant (1.3- to 1.6-fold) apparent reduction of the membrane surface area in the dormant spore relative to that in the germinated spore, but is not due to the dormant spore's high levels of dipicolinic acid and divalent cations.